Metaplasmos da língua portuguesa: uma aplicação na rede social digital Facebook - TEIXEIRA, Antônia Nádia dos Santos (2019)
The present work falls within the field of sociolinguistics and historical grammar, for being dedicated to analyze processes of linguistic variation and evolution of the language from the study of words in the digital social network facebook. In this way, the objective was to analyze the occurrence of metaplasms in the posts of this medium with the purpose of identifying this phenomenon (metaplasm) as a linguistic variation, which is manifested in the language through the social network facebook, being used in diverse interactions, for being conditioned to a cyberculture and to specific communicative functions of language use. Based on the theories of Coutinho 1976), Botelho and Leite (s / d), Câmara Jr. (1884), Dias (2015), Labov (2008), Bagno (2008), Marcushi (2007), Coseriu Saussure (2006), Bronckart (2003), Fiorin (2008) and Lévy (1999). The corpus of this work will consist of fifteen (fifteen) images (posts made by facebook users), in which a synchronic cut of the object of study will be done, which are words that when written on this digital platform were transformed phonetically to fulfill some communicative function , emotive or just phonetic fist use of the language.